Communication approach of Gopay’s digital alms platform - Santoso, Budi; Randa, Agrian Ratu; Suryana, Asep; Prihatini, Lishapsari; Yenrizal, Yenrizal (Jurnal Kajian Komunikasi, 2023)
Background: According to the 2018 World Giving Index by the Charities Aid Foundation (CAF), Indonesia ranked first in the world giving index for the first time. However, the emergence of digital alms practices in Indonesia has sparked controversy surrounding their compliance with usury laws, a deeply held belief in Islam. This has created an enigma within the Islamic community, as the Indonesian Ulema Council works to establish legitimacy for these practices. Given the multi-layered nature of these practices in society. Purpose: This paper aims to elucidate how the provider, specifically GoPay in this case, communicates digital alms to the public and how the Islamic community in Indonesia perceives and accepts it as a customary practice. Method: A qualitative research approach was employed for this article, focusing on conducting in-depth interviews and examining future studies and regulations pertaining to digital alms programs. Results: The findings of this study indicate that the implementation of digital alms programs has prompted a shift in the community’s giving habits from traditional direct methods to digital methods. This shift offers convenience to donors, who now have numerous options available to them. However, it is important to note that traditional beliefs surrounding alms emphasize direct interaction between the giver and the receiver, raising concerns about the potential for manipulation of alms before they reach the intended recipients. While this innovation has gained significant traction within the Islamic community, the use of financial technology introduces the possibility of inaccuracies and raises questions about the acceptance of its processes. Therefore, additional coordination and oversight with relevant parties are needed. Conclusion: Introducing digital alms programs has engendered new practices within the community for activities like almsgiving, enabling cashless transactions. However, there are still challenges to address, including ensuring the reliability and integrity of the process. This requires collaboration and supervision among stakeholders. Implications: The introduction of digital alms programs has prompted a transformation in community practices related to almsgiving and similar activities by embracing cashless methods.